2017
DOI: 10.1002/ece3.3573
|View full text |Cite
|
Sign up to set email alerts
|

Regional patterns of increasing Swiss needle cast impacts on Douglas‐fir growth with warming temperatures

Abstract: The fungal pathogen, Phaeocryptopus gaeumannii, causing Swiss needle cast (SNC) occurs wherever Douglas‐fir is found but disease damage is believed to be limited in the U.S. Pacific Northwest (PNW) to the Coast Range of Oregon and Washington (Hansen et al., Plant Disease, 2000, 84, 773; Rosso & Hansen, Phytopathology, 2003, 93, 790; Shaw, et al., Journal of Forestry, 2011, 109, 109). However, knowledge remains limited on the history and spatial distribution of SNC impacts in the PNW. We reconstructed the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…Previous studies have identified significant associations between environmental variables, colonization by N. gaeumannii, and SNC symptoms (Coop & Stone, 2010;Hansen et al, 2000;Lee et al, 2013Lee et al, , 2017Manter et al, 2005;Rosso & Hansen, 2003;Shaw, Woolley, & Kanaskie, 2014;Stone, Coop, et al, 2008;Stone et al, 2007;Watt et al, 2010;Zhao et al, 2012Zhao et al, , 2011 Given that the occlusion of stomata causes the foliage loss associated with SNC, we expected the correlation between AFR and CI to be stronger, as reported in previous studies (Manter et al, 2003;Watt et al, 2010). In our dataset, there was considerable variation in AFR for a given value of CI, suggesting genetic variation in host tolerance (i.e., some host genotypes can tolerate higher levels of infection before needle abscission occurs) and/or that AFR may be affected by environmental factors in combination with SNC severity.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have identified significant associations between environmental variables, colonization by N. gaeumannii, and SNC symptoms (Coop & Stone, 2010;Hansen et al, 2000;Lee et al, 2013Lee et al, , 2017Manter et al, 2005;Rosso & Hansen, 2003;Shaw, Woolley, & Kanaskie, 2014;Stone, Coop, et al, 2008;Stone et al, 2007;Watt et al, 2010;Zhao et al, 2012Zhao et al, , 2011 Given that the occlusion of stomata causes the foliage loss associated with SNC, we expected the correlation between AFR and CI to be stronger, as reported in previous studies (Manter et al, 2003;Watt et al, 2010). In our dataset, there was considerable variation in AFR for a given value of CI, suggesting genetic variation in host tolerance (i.e., some host genotypes can tolerate higher levels of infection before needle abscission occurs) and/or that AFR may be affected by environmental factors in combination with SNC severity.…”
Section: Discussionmentioning
confidence: 97%
“…Included as vectors on the joint plot were SNC severity (AFR and CI), the relative proportion of Lineage 2, latitude, longitude, elevation, and several environmental variables related to SNC severity and N. gaeumannii abundance (Lee et al, 2017;Manter et al, 2005;Rosso & Hansen, 2003;Stone, Coop, et al, 2008;Stone et al, 2007;Watt et al, 2010;Zhao et al, 2011). Included as vectors on the joint plot were SNC severity (AFR and CI), the relative proportion of Lineage 2, latitude, longitude, elevation, and several environmental variables related to SNC severity and N. gaeumannii abundance (Lee et al, 2017;Manter et al, 2005;Rosso & Hansen, 2003;Stone, Coop, et al, 2008;Stone et al, 2007;Watt et al, 2010;Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations